2004
DOI: 10.1111/j.1468-5884.2004.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

On the saliency of negative stimuli: Evidence from attentional blink1

Abstract: When people are asked to detect two targets from a rapid serial visual presentation (RSVP) stream, impairment of recognition of the second target (T2) can be observed if the T2 is presented several hundred milliseconds later than the first target (T1). This phenomenon is known as attentional blink, and is considered to reflect some temporal characteristic of the attentional process. The aim of the present study was to use the attentional blink paradigm to examine whether the affective meaning of the stimuli co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
43
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 22 publications
(41 reference statements)
9
43
3
1
Order By: Relevance
“…Allocating attention to T1 is thought to leave less attention available for T2, rendering T2 vulnerable to decay or substitutionhence the transient 'blink' in attention (for review, see Shapiro et al 1997). However, the size of the attentional blink is greatly attenuated if T2 stimuli are emotionally charged (Anderson and Phelps 2001;Anderson 2005;Ogawa and Suzuki 2004;Arend and Botella 2002). This affective modulation of the attentional blink is most evident when T1 and T2 are close together, which is when attentional resources are most occupied with the processing of the preceding T1.…”
Section: Introductionmentioning
confidence: 97%
“…Allocating attention to T1 is thought to leave less attention available for T2, rendering T2 vulnerable to decay or substitutionhence the transient 'blink' in attention (for review, see Shapiro et al 1997). However, the size of the attentional blink is greatly attenuated if T2 stimuli are emotionally charged (Anderson and Phelps 2001;Anderson 2005;Ogawa and Suzuki 2004;Arend and Botella 2002). This affective modulation of the attentional blink is most evident when T1 and T2 are close together, which is when attentional resources are most occupied with the processing of the preceding T1.…”
Section: Introductionmentioning
confidence: 97%
“…The contrast of interest-the difference between positive and neutral stimuli-had to be assessed and tested through a within-subject design. Very few studies tested the contrast of interest with a between design (Mak-Fan, Thompson, & Green, 2011;Ogawa & Suzuki, 2004); given the potential bias in combining between and within designs in the same meta-analysis (Morris & DeShon, 2002), we decided not to include studies that used a between-subjects design.…”
Section: Methods Inclusion Criteriamentioning
confidence: 99%
“…Several studies have shown that the AB is attenuated for highly arousing T2 words (Anderson, 2005;Anderson & Phelps, 2002;Keil & Ihssen, 2004;Keil, Ihssen, & Heim, 2006). Other studies have shown that participants' own name (Shapiro, Caldwell, & Sorensen, 1997), familiar faces (Jackson & Raymond, 2006), and negatively valenced ideographs (Ogawa & Suzuki, 2004) "survive" the AB as well.…”
Section: Introductionmentioning
confidence: 99%